Influence of mineral admixtures on mechanical properties of self‐compacting concrete under elevated temperature. (November 2016) - N, Anand; I, Antony Godwin; G, Prince Arulraj
SUMMARY: Self‐compacting concrete (SCC) is a form of concrete that is capable of flowing into the congested interior of formwork and consolidating under the action of its own weight without segregation and bleeding. In the present investigation, an attempt has been made to study the effect of elevated temperature on mechanical properties of SCC specimens made with different mineral admixtures that were heated from 27 to 900 °C and cooled by air or water. Silica fume, flyash, metakaolin were used as mineral admixtures. Master Glenium was used as superplasticizer, and Glenium Stream 2 was used as viscosity modifying agent. Mechanical properties of the cooled specimens such as compressive strength, tensile strength, flexural strength, and modulus of elasticity were found. Compressive, tensile, and flexural strengths of specimens were found to decrease by 73.18%, 65.05%, and 63.2%, and 85.2%, 83.52%, and 83.56% for the specimens with metakaolin that were heated and cooled by air and water, respectively. Similar reductions were found for the SCC specimens made with silica fume and flyash. Microstructure investigation has been carried out on SCC samples using scanning electron microscope and X‐ray diffraction analytical techniques to understand the effect of temperature on decrease in strength. Copyright © 2016 John Wiley & Sons, Ltd.